Commemoration of the first centenary of the Battle of Ayacucho in Lima The building of the Hotel Bolivar - Barrera, Henry (2023)
The battle of Ayacucho took place on December 9, 1824, and meant the consolidation of the proclamation of independence made in 1821. Given the proximity of the comme- moration of the first centenary of this historical event, Lima got prepared to receive the foreign delegations that would come to witness the various celebrations. In this context, the construction of a modern hotel that would house visitors was prioritized, with the Hotel Bolívar being inaugurated in 1924. This research analyzes the process followed for such a monumental work to be executed and, through primary sources, will demonstrate the relationship between architecture and patriotic celebrations.